Penggunaan Multimedia Berbasis Komputer - Habib Tolhah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
The extent and amount of social studies material, requires creative and innovative teachers in the Learning Process to be lively and dynamic, social studies teachers must be able to change the paradigm that social studies lessons are only interesting, boring stories. This Classroom Action Research (CAR) discusses innovation in the learning process through multimedia to improve the quality of student achievement. The problem discussed is how the use of computer-based multimedia in group discussions can improve the learning outcomes of social studies students of class IX A of SMP Negeri 1 Bumiayu in Semester I of the Academic Year 2013/2014 This study was conducted in 2 cycles, with the conclusion that, there was an increase in student learning outcomes from pre-action to action 2. In the Pre-complete Action KKM 12 students or 33.33%. Action 1 student who finished KKM 20 students or 66.66%. While the action of 2 students was completed KKM 36 students or 100%.